Soudabeh DESIRES: Gender Performativity and Performance of Gender, from Ancient Mythologies to Present Street Performances - Kalami, Proshot (Margins/Marges/Margini, 2025)
This research investigates how ancient female figures, particularly Soudabeh/Phaedra, inform Iranian artists and activists in the Woman, Life, Freedom movement. Focusing on the myth of Siyavash from Ferdowsi’s Shahnameh, Biblical Joseph and Zuleikha, and Greco-Roman Phaedra and Hippolytus, I challenge patriarchal master narratives to reimagine gender identity and the politics of desire in contemporary protest performances of women. I investigate if the marginalised past is projected in the present creations of a new vision of gender identity and desire from a non-patriarchal perspective. Therefore, the real question to explore is how we may transform deeply embedded systems that currently centre white supremacy cultures and transactional ways of knowing and doing. Adopting a decolonial lens, I critique Western theories of gender performativity, therefore examining how Iranian women disrupt such epistemologies in their performances of gender in their practices of everyday life.